2013
DOI: 10.1002/adma.201301985
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Transparent Polymer Solar Cells with Excellent Sub‐Bandgap Transmission for Third Generation Photovoltaics

Abstract: Semi-transparent organic photovoltaics are of interest for a variety of photovoltaic applications, including solar windows and hybrid tandem photovoltaics. The figure shows a photograph of our semi-transparent solar cell, which has a power conversion efficiency of 5.0%, with an above bandgap transmission of 34% and a sub-bandgap transmission of 81%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 51 publications
0
57
1
Order By: Relevance
“…Recent progress has shown that visibly transparent polymer solar cells produced by solution processing could be integrated into glass substrates as well (Figure 15 B). [ 441,444 ] A stacked transparent battery and solar cell device (for example, considering device shown in Figure 15 A stacked on top the one shown in Figure 15 B) will absorb some 50% of light and could operate as a stand-alone energy source, powering and storing the energy for the building. If REVIEW wileyonlinelibrary.com 6% effi cient window PVs were used to entirely cover the same Willis Tower, it would generate nearly 5.3 GWh of energy per year.…”
Section: Optically Active Schemes/confi Gurationsmentioning
confidence: 99%
“…Recent progress has shown that visibly transparent polymer solar cells produced by solution processing could be integrated into glass substrates as well (Figure 15 B). [ 441,444 ] A stacked transparent battery and solar cell device (for example, considering device shown in Figure 15 A stacked on top the one shown in Figure 15 B) will absorb some 50% of light and could operate as a stand-alone energy source, powering and storing the energy for the building. If REVIEW wileyonlinelibrary.com 6% effi cient window PVs were used to entirely cover the same Willis Tower, it would generate nearly 5.3 GWh of energy per year.…”
Section: Optically Active Schemes/confi Gurationsmentioning
confidence: 99%
“…There are several organic-based approaches that produce semi-transparent OPV devices that exhibit good electrical performance (Figure 8), whereby they are composed of organic electronic materials, and transparent electrodes based on a wide range of different materials, including conducting polymers [122][123][124][125], thin metal films [126], sputtered transparent conducting oxides of LiCoO2/Al [127], carbon nanotubes [122], graphene [128], and silver nanowires (Ag NWs) [129][130][131][132][133]. Recently, a study by Beiley et al [134], has shown the development of a semi-transparent OPV which consists of a silver nanowire (Ag NW) and zinc oxide nanoparticle (ZnO NP) composite top electrode, and has a power conversion efficiency of 5.0%. Additional studies have indicated that Ag NWs can be used as an efficient top electrode for semi-transparent OPV systems where P3HT:PCBM is used [129].…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…This Ag NW ZnO NP composite top electrode produced by Beiley et al [134] shows great compatibility for solar glazing production, whereby it has low sheet resistance (14 Ω·sq −1 ) required for large scale module manufacturing, and it is also processed in solution, making it particularly suitable for low-cost, high throughput fabrication techniques that are favoured in the glazing industry.…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…Several different options have been considered, such as low-temperature annealed indium tin oxide (ITO), [42][43][44][45][46][47][48] a three-layer architecture combining a dielectric layer, an ultra thin metal layer, and a second dielectric layer, [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] PEDOT, [65][66][67] silver grid, 68 graphene, [69][70][71] carbon nanotubes, 67,72 and silver nanowires (AgNW). [73][74][75][76][77][78] However, the need for a nondestructive deposition technique for the top semi-transparent electrode is probably not the major issue that semi-transparent OPV cells must overcome before becoming an industrially viable solution. Indeed, when the top electrode of an OPV cell is made semi-transparent, the capacity of the solar device to trap the electromagnetic field in the absorber layer diminishes.…”
Section: Introductionmentioning
confidence: 99%